Analysis of Game Method Training on Tackle Ability in Rugby Game - Aji Zaelanir; Encep Sudirjo; Muhammad Nur Alif (Universitas Pendidikan Indonesia, 2022)
This research is based on the researcher's curiosity about the relationship between the Tackle Drill Game Method and the Tackle Rugby Ability as well as the lack of ability or technique to tackle (dropping opponents) on the Upi Sumedang campus rugby athletes. Therefore, the researcher wanted to find out whether the Tackle Drill Game Method has a good potential for success in the Tackle ability in the game of Rugby. The research method used is literature study, which examines data or theories put forward by previous researchers. Thus this study only compares whether there is a relationship, linkage or similarity of characteristics between the two variables to be studied. In practice, the researchers found that the tackle drill game method affects rugby tackle ability on the basis of saying that this drill training method makes an athlete have to perform the movements instructed by the coach repeatedly so that it allows an athlete to become accustomed (automatically) in performing a movement .